PENGARUH CUSTOMER REVIEW DAN KUALITAS PELAYANAN TERHADAP MINAT PENGGUNAAN LAYANAN DIMEDIASI BRAND TRUST PADA TRANSPORTASI ONLINE MAXIM DI GENERASI Z - Sidiq, Adam Maulana; Hadita, Hadita; Komariah, Neng Siti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The rapid technological advancement in Indonesia, particularly in online motorcycle taxi services, has been remarkable. One online ride-hailing application that has successfully gained popularity is Maxim, offering efficient and convenient transportation services to its users. Consumers are increasingly considering customer reviews and service quality when deciding to use online motorcycle taxi services. This research aims to analyze the extent to which customer reviews and service quality influence the interest in using the Maxim online ride-hailing application, with brand trust acting as a mediator. Using a quantitative method, this study collected data from respondents in the Bekasi region.The findings indicate that customer reviews and service quality have a significant impact on interest in usage, mediated by brand trust. Therefore, service providers need to ensure robust strategies to enhance positive customer reviews and maintain excellent service quality to build strong brand trust, thereby increasing user interest